Annotated zoogeography of non-marine Tardigrada. Part III: North America and Greenland - Kaczmarek, Łukasz; Michalczyk, Łukasz; Mcinnes, Sandra J. (Zootaxa, 2016)
This paper is the third monograph of the series that describes the global records of limno-terrestrial water bears (Tardigrada). Here, we provide a comprehensive list of non-marine tardigrades recorded from the North America, providing an updated and revised taxonomy accompanied by geographic co-ordinates, habitat, and biogeographic comments. It is hoped this work will serve as a reference point and background for further zoogeographical and taxonomical studies.